2012
DOI: 10.1007/s00228-012-1250-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and safety of raltegravir in pregnancy

Abstract: Dear Sirs:The aim of anti-HIV treatment in pregnancy is the suppression of the HIV-1 RNA viral load in the plasma before delivery [1] to prevent mother-to-child transmission of the infection. The achievement of this outcome may be complicated in pregnant women who have been treated with multiple drugs by the lack of active drugs available. Although there are limited data on the use of the integrase inhibitor raltegravir in pregnancy, the availability of this drug is important in the management of multidrug-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Protease inhibitors, such as atazanavir (22,23) and lopinavir (20,24) actively cross the placenta; however, undetectable concentrations in cord blood have been reported for nelfinavir, indinavir, and saquinavir (25,26). Fusion/entry inhibitors cross poorly into cord blood (7,11). The human placenta plays a major role in maternal-to-fetal and fetal-to-maternal transfer of nutrients and oxygen and of waste products, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protease inhibitors, such as atazanavir (22,23) and lopinavir (20,24) actively cross the placenta; however, undetectable concentrations in cord blood have been reported for nelfinavir, indinavir, and saquinavir (25,26). Fusion/entry inhibitors cross poorly into cord blood (7,11). The human placenta plays a major role in maternal-to-fetal and fetal-to-maternal transfer of nutrients and oxygen and of waste products, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have measured the PK of INSTIs during pregnancy (6). RTG has been shown to cross the placenta well, with drug concentrations detected in cord blood plasma from mothers receiving this ARV during pregnancy (11,14). DTG has also been shown to readily cross the blood-placenta barrier (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Croci et al reported a trough level of raltegravir of 0.21 µg/mL in the third trimester in one patient, compared to median trough concentrations in a trial of non-pregnant adults of 0.029–0.118 µg/mL. 7 Maternal plasma raltegravir at delivery was 0.19 µg/mL with cord:maternal ratio of 1.0. 7 In another case report, the maternal trough level was 0.162 µg/mL, cord blood was 0.173 µg/mL and a cord:maternal ratio of 1.06.…”
Section: Introductionmentioning
confidence: 95%
“…7 Maternal plasma raltegravir at delivery was 0.19 µg/mL with cord:maternal ratio of 1.0. 7 In another case report, the maternal trough level was 0.162 µg/mL, cord blood was 0.173 µg/mL and a cord:maternal ratio of 1.06. 6 In a case series from London, maternal levels near delivery ranged from 0.022–0.493 µg/mL five to 13 hours after maternal dosing, and levels in infant blood one to three hours after delivery ranged from seven to nine times higher than concomitant maternal levels.…”
Section: Introductionmentioning
confidence: 97%